Effects of global liquidity on commodity and food prices - Ansgar Belke; Ingo G. Bordon; Ulrich Volz (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
This paper investigates the relationship between global liquidity and commodity and food prices applying a global cointegrated vector-autoregressive model. We use different measures of global liquidity and various indices of commodity and food prices for the period 1980-2011. Our results support the hypothesis that there is a positive long-run relation between global liquidity and the development of food and commodity prices, and that food and commodity prices adjust significantly to this cointegrating relation. Global liquidity, in contrast, does not adjust, it drives the relationship.
Keywords: E52; E58; C32; 330; Commodity prices; food prices; global liquidity; cointegration; CVAR analysis